2000
DOI: 10.1901/jaba.2000.33-85
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Establishing Operations on Preference Assessment Outcomes

Abstract: Preference assessments were conducted for 4 individuals with developmental disabilities across conditions of (a) control, allowing equal access to all stimuli prior to the preference assessment; (b) deprivation, allowing no access to one stimulus for 48 hr prior to the assessment; and (c) satiation, allowing free access to one stimulus for 10 min immediately prior to the assessment. Deprivation resulted in increased preference, whereas satiation resulted in decreased preference compared to control conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 4 publications
3
39
0
3
Order By: Relevance
“…Responding decreased in both the ediblereinforcement and token-reinforcement conditions when participants were given unlimited pre-session access to the HP-edible. These results replicate and extend the research by Gottschalk et al (2000) who showed that preferences for edible items increased under deprivation and decreased under satiation conditions. In the current study, similar results were observed for both edibles and tokens, demonstrating empirically that AOs affect non-generalized conditioned reinforcers similarly to primary reinforcers.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Responding decreased in both the ediblereinforcement and token-reinforcement conditions when participants were given unlimited pre-session access to the HP-edible. These results replicate and extend the research by Gottschalk et al (2000) who showed that preferences for edible items increased under deprivation and decreased under satiation conditions. In the current study, similar results were observed for both edibles and tokens, demonstrating empirically that AOs affect non-generalized conditioned reinforcers similarly to primary reinforcers.…”
Section: Resultssupporting
confidence: 91%
“…Tokens that are sensitive to MOs are, by definition, non-generalized conditioned reinforcers. These results replicate and extend the research by Gottschalk et al (2000), in which it was demonstrated that preferences for edible items increased under deprivation and decreased under satiation conditions. Experiment 3 sought to identify the number of backup reinforcers with which a token must be paired in order to make the token insensitive to AO effects, that is, the number of pairings sufficient to establish the token as a generalized conditioned reinforcer.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is likely followed by what is traditionally referred to as a rekindling after a conflict and might have a positive effect on the quality of interactions. Concurrently, the victim experiences deprivation of interacting with the offender that not only increases the likelihood he or she will forgive, but also reduces the response requirements for sufficient apologies (for a related applied example, see Gottschalk, Libby, & Graff, 2000). Therefore, apologetic response forms that were extinguished during conflict might be reinforced following time apart.…”
Section: Deprivation (Time Without Interaction)mentioning
confidence: 99%
“…Each session ended in a reinforcer condition and the entire procedure was repeated three times in order to ensure reliability (DeLeon, et al, 2009). Gottschalk, Libby and Graff (2000) have shown that stimuli which had previously been demonstrated as being least preferred may function as reinforcers in subsequent circumstances; thus the pool of games available as reinforcers remained consistent among trials in order to minimize possible confounds impacting internal validity. A frequency count was taken for each time the child elected to engage in TO or WN and the mean break points for each subject were calculated across repeated conditions…”
Section: Progressive Ratio Punishmentmentioning
confidence: 99%